POLYMORPHISM AND FEATURES OF VEGETATIVE PROPAGATION OF THUJA OCCIDENTALIS L. BY DECORATIVE FORMS CUTTING - Lisoviy, M. М.; Guz, M. М. (Forestry and Forest Melioration, 2018)
Introduction Green areas in urban ecosystems perform a significant sanitary and ecological role in the improvement the human environment .Today one of most popular types in landscaping both municipal and private is Thuja occidentalis L. The wide forms diversity of Thuja occidentalis L. makes it possible to use the plant in landscape gardening compositions both of regular and landscape planning, leading to a significant relevance of research methods of reproduction of decorative forms of Thuja occidentalis L. and its polymorphism. Aim of this work was to study the polymorphism of Thuja occidentalis L. and to improve the vegetative reproduction methods of decorative forms of studied species i. e. selection of optimal timing of harvesting cuttings, determination of type and concentration of rooting stimulant and soil substrate. Materials and Methods The objects of the research were decorative forms of Thuja occidentalis L., which is most common in the landscaping areas of different functions. Intraspecific variability of Thuja occidentalis L. (polymorphism) was examined and have classified by analyzing the literature. For reproduction of studied forms of Thuja occidentalis L. cuttings were selected because this method is based on the phenomenon of totipotent and accordingly allows getting posterity genetically identical to the parent plant. Experiments on the reproduction of decorative forms of Thuja occidentalis L. were conducted on the territory of decorative nursery of State Botanical Garden of Ukrainian National Forestry University (Lviv) by conventional methods. In general, the whole process can be divided into the following stages: choosing mother plants; harvesting cuttings; treat cuttings with root stimulants; planting cuttings in the substrate, tending and accounting of cuttings that have had root. Results The paper briefly describes the biological characteristics of Thuja occidentalis L., presents ways of its application in the landscape art and formulates the relevance of the studies. In addition, a brief description of the most common in the landscape decorative forms of studied species is given. Vegetative reproduction of the following species decorative forms: 'Aurea', 'Smaragd', 'Bodmeri', 'Danica nana' and 'Elegantissima' was experimentally studied using different rooting stimulants. The obtained results show that ligneous cuttings treated with a stimulant “Нeteroauxin Super” is the most efficiently for reproduction of decorative forms of Thuja occidentalis L. In this case, rooting amounts to 86-92 % for corresponding decorative forms. In the case of propagation by green cuttings we received somewhat lower results in all variants of the experiment and the best stimulant was “Kornevin” which provides from 66 to 82 % rooted cuttings. Conclusions Thuja occidentalis L. is a polymorphic species (there are more than 250 decorative forms). The results of vegetative reproduction of studied decorative forms of Thuja occidentalis L. show that using of ligneous cuttings treated with stimulant “Нeteroauxin Super” provides the highest percentage of rooting. The most successful rooting of green cuttings was obtained using commercial formulation “Kornevin”.